Antagonistic Test of Endophytic Fungi from Black Pepper (Piper nigrum L.) against Fusarium oxysporum the Main Cause of Fusarium Wilt in Chili Plants (Capsicum annuum L.) - Sofian, Sofian; Sopialena, Sopialena; Aprilia, Risna (CV. Komunitas Dunia Peternakan, 2025)
Fusarium wilt, caused by Fusarium oxysporum, is a major constraint in chili (Capsicum annuum L.) cultivation due to its severe impact on plant health and yield. Excessive use of synthetic fungicides to control this disease has resulted in environmental pollution and the development of resistant pathogens. This study aimed to identify endophytic fungi from black pepper (Piper nigrum L.) and evaluate their antagonistic potential against F. oxysporum as an eco-friendly biological control strategy. The novelty of this research lies in the exploration of endophytic fungi from black pepper, a crop not commonly studied as a microbial reservoir for chili disease control, providing new insight into cross-host endophytic interactions and their potential application in sustainable plant protection. Endophytic fungi were isolated from the stems, roots, and leaves of healthy black pepper plants, while F. oxysporum isolates were obtained from diseased chili plants. All isolates were cultured on Potato Dextrose Agar (PDA) and tested using a dual culture assay under a completely randomized design (CRD) with five treatments and six replications. Inhibition percentage and colony growth were observed for seven days, and antagonistic mechanisms such as competition, antibiosis, and parasitism were examined microscopically. Four endophytic fungi—Trichoderma sp., Gliocladium sp., Aspergillus niger, and Aspergillus flavus—showed antagonistic activity against F. oxysporum. The highest inhibition rates (60–75%) were observed in Gliocladium sp. and Trichoderma sp., primarily through competition and antibiosis mechanisms. These results demonstrate the potential of black pepper-derived endophytic fungi as novel, effective, and environmentally safe biocontrol agents, offering an innovative approach to developing sustainable alternatives to synthetic fungicides in integrated plant disease management systems.